A Chinese Take(Away) of Brahms: How The Singapore Chinese Orchestra Courted Europe - Tan Shzr Ee, (Wacana Seni Journal of Arts Discourse, 2012)
In March 2005, the Singapore Chinese Orchestra (SCO) embarked on its debut European tour in Budapest and London, taking two programmes in anticipation of different cultural expectations. In Budapest, it presented, among other pieces, Johannes Brahms' Hungarian Dance No. 5 and Bela Bartok's Romanian Dances. In London: avant-garde and film composers Tan Dun and Michael Nyman. This article briefly tracks the background of Chinese orchestral music in Singapore, and examines the articulation of its contemporary Asianness on two platforms where the West has taken on different guises of The Other. Apart from challenges in transplanting cross-cultural aesthetics as an extension of an old game played over the past 60 years of Chinese orchestral development, the SCO's European tour threw up discussions on situational identity, representation and reception in the cross-wiring of Singaporean state agenda, commercial enterprise, artistic aspiration and historical makeup. This case study seeks to deconstruct an orchestral sales pitch in terms of a layered musical, sociological and transcultural courtship.